Risky Sexual Behavior of Young Adults in Hong Kong: An Exploratory Study of Psychosocial Risk Factors - Chan, Heng Choon (Oliver) (Frontiers in Psychology, 2021)
There is limited knowledge of the prevalence and nature of risky sexual behavior (RSB) among young adults in Hong Kong. This cross-sectional study explored the psychosocial risk factors of RSB with a sample of 1,171 Hong Kong university students (aged 18–40 years). Grounded in the theoretical propositions of several criminological theories (i.e., the theories of self-control, general strain, social learning, social control, and routine activity), engagement in three types of RSB (i.e., general, penetrative, and non-penetrative) was studied alongside a range of psychosocial risk factors. Relative to female participants, male participants reported significantly higher mean levels of general, penetrative, and non-penetrative RSB. Male participants also reported significantly higher mean levels of negative temperament, use of alcohol and other drugs, and paraphilic interests than female participants, who reported significantly higher mean levels of self-control and social bonds than their male counterparts. The results of multivariate analyses (i.e., OLS regressions) revealed that, to a large extent, the male and female participants shared a similar set of psychosocial risk factors (i.e., use of alcohol and other drugs, and paraphilic interest) for their involvement in general, penetrative, and non-penetrative RSB. Furthermore, a high level of negative temperament was significantly associated with penetrative RSB for both genders, while a high level of perceived neighborhood disorganization was found to be an important factor in the participation of females in general, penetrative, and non-penetrative RSB. The findings of this study may have important implications for practice in regard to reducing, if not entirely preventing, the tendency to engage in RSB.